2011
DOI: 10.1186/1471-244x-11-68
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting staff morale on inpatient mental health wards in England: a qualitative investigation

Abstract: BackgroundGood morale among staff on inpatient psychiatric wards is an important requirement for the maintenance of strong therapeutic alliances and positive patient experiences, and for the successful implementation of initiatives to improve care. More understanding is needed of mechanisms underlying good and poor morale.MethodWe conducted individual and group interviews with staff of a full range of disciplines and levels of seniority on seven NHS in-patient wards of varying types in England.ResultsInpatient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
65
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 19 publications
8
65
1
Order By: Relevance
“…However, some staff appeared to place the onus for responsibility of engagement on the service user rather than on staff; some staff reported that their unit's service users were too unwell to engage, or that the GetREAL teams had been successful in this because they had happened to be on the unit at a time when the service users were somehow easier to engage. Although it may be true that the profile of service users has changed to some degree over recent decades, with the development of an increasingly community-based mental health system (such that those patients in hospital are at the most severe end of the spectrum), 88 these are, nevertheless, the patients that contemporary mental health rehabilitation services work with. Furthermore, the positive impact on staff and service users reported during the enabling stage suggests that many service users could be engaged successfully in activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some staff appeared to place the onus for responsibility of engagement on the service user rather than on staff; some staff reported that their unit's service users were too unwell to engage, or that the GetREAL teams had been successful in this because they had happened to be on the unit at a time when the service users were somehow easier to engage. Although it may be true that the profile of service users has changed to some degree over recent decades, with the development of an increasingly community-based mental health system (such that those patients in hospital are at the most severe end of the spectrum), 88 these are, nevertheless, the patients that contemporary mental health rehabilitation services work with. Furthermore, the positive impact on staff and service users reported during the enabling stage suggests that many service users could be engaged successfully in activities.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of permission also relates to the low degree of decision-making autonomy many staff felt they had in inpatient settings. 88 This, in turn, presumably reinforced inflexibility in role boundaries and remit. It is also likely to have impacted on staff morale and ward atmosphere.…”
Section: Discussionmentioning
confidence: 99%
“…Day, Minichiello, and Madison (2007) state that, in order for morale to be improved, there must be a shared vision of what both management and employees are trying to accomplish together, as well as an understanding of the problems and pressures on both groups. Totman, Hundt, Wearn, Paul, and Johnson (2011) argues that organizational variables that were associated with employees' morale indicators were staff ratings of role clarity, team communication, and perceived fairness in the work environment. Finally, Gallie, Zhou, Felstead, and Green (2012) note that the positive aspects of introducing team working are linked to increases in task discretion and job satisfaction.…”
Section: Teamwork and Its Relationship To Moralementioning
confidence: 99%
“…found that among staff, feelings of agency towards psychotic patients seemed to increase when they were helped to develop psychological formulations concerning individual patients. In a study on inpatient mental health wards, Totman et al (2011) identified various factors that had positive influences on staff morale, which is an important part of agency. These included good relationships with colleagues, a culture of openness and acceptance, informal support from managers, spending time with patients, and seeing them get better.…”
Section: Professional Agencymentioning
confidence: 99%